2015
DOI: 10.1136/acupmed-2015-010765
|View full text |Cite
|
Sign up to set email alerts
|

Laser Acupuncture before Heel Lancing for Pain Management in Healthy Term Newborns: A Randomised Controlled Trial

Abstract: KA14/09.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(78 citation statements)
references
References 31 publications
0
78
0
Order By: Relevance
“…Significant pain reduction has been demonstrated in two studies, one with laser acupuncture with 30 mW at LI 4 and Shen Men and the other with light needling at Yin Tang [ 13 , 14 ]. One study with acupressure showed equal pain scores and one higher pain scores in neonates treated with laser acupuncture with 10 mW at Yin Tang [ 15 , 16 ]. The latest study showed significant pain reduction with NESAP combined with oral sucrose solution [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant pain reduction has been demonstrated in two studies, one with laser acupuncture with 30 mW at LI 4 and Shen Men and the other with light needling at Yin Tang [ 13 , 14 ]. One study with acupressure showed equal pain scores and one higher pain scores in neonates treated with laser acupuncture with 10 mW at Yin Tang [ 15 , 16 ]. The latest study showed significant pain reduction with NESAP combined with oral sucrose solution [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Five other studies investigated acupuncture for pain prevention before heel lance. The first trial demonstrated a significant reduction of pain score PIPP (Premature Infant Pain Profile) [ 13 ], one of these showed a reduction of pain score NIPS (Neonatal Infant Pain Scale) and crying duration [ 14 ], one illustrated a reduced cry and treatment duration [ 15 ], one showed no effect concerning NIPS [ 16 ], and the latest trial demonstrated significantly higher PIPP scores only with NESAP (noninvasive stimulation of acupuncture points) and lower PIPP scores with NESAP combined with sucrose solution [ 17 ]. The most frequently used acupuncture point in these trials was Large Intestine 4 (Abbreviation: LI 4, in Chinese: He Gu) [ 10 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For heel lancing pain in infants, LA was shown to be less effective than oral sucrose [2]. However, this study had numerous limitations including using only one acupoint, no comparison as an adjunct pain tool in the control group, and the low 0.3 J dose per point.…”
Section: Discussionmentioning
confidence: 99%
“…Abbasoglu et al [15] indicated that laser acupuncture (LA) with 1.125 microjoules of energy at the Yintang point two minutes prior to heel lancing is less effective than oral sucrose for reducing the discomfort of this procedure. We found shorter procedure time in the LA group compared to the oral sucrose group, but longer crying time and worse NIPS scores in the LA group.…”
Section: Methodsmentioning
confidence: 99%